2017
DOI: 10.1177/0969733017694498
|View full text |Cite
|
Sign up to set email alerts
|

The silent world of young next of kin in mental healthcare

Abstract: The study finds a need for more family-oriented perspectives in both mental healthcare practices and healthcare ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…As shown in Fig. 1, 26 23 papers were selected: 12,16, 16 reported on the experiences of carers only, 12,16,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] while seven reported on the experiences of patients, carers and other stakeholders. [27][28][29][30][31][32][33] Study characteristics are summarised in supplementary Table 1 including quality appraisal results that show that 20 of the 23 papers were rated as high-quality studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As shown in Fig. 1, 26 23 papers were selected: 12,16, 16 reported on the experiences of carers only, 12,16,[34][35][36][37][38][39][40][41][42][43][44][45][46][47] while seven reported on the experiences of patients, carers and other stakeholders. [27][28][29][30][31][32][33] Study characteristics are summarised in supplementary Table 1 including quality appraisal results that show that 20 of the 23 papers were rated as high-quality studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thus, the results from this study are consistent with findings from the main project (PET). 11 However, the previous article in the main project found that young next-of-kin wanted more contact with their family members during hospital admittance. 11 To a certain degree, this point diverges from the findings in the current study, in that there were different views and uncertainty among the participants about whether the young next-of-kin wanted to have distance or more close contact with their close relatives during times of admittance.…”
Section: What Needs Do Young Next-of-kin In Coercion-related Situatiomentioning
confidence: 95%
“…Even though the data are five years old, there are only a few recent studies exploring similar problems. 7,11,24 By interviewing the CRS, we gained access to key informants in the field. However, additional observational data on how CRS deals with these challenges in practice would have been beneficial.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations